Ghostly Past. On Jean Améry’s At the Mind’s Limits - Bugajewski, Maciej (Sensus Historiae, 2019)
In this article I focus on the essay How Much Home Does a Person Need? by Jean Améry. I analyze the difference between traditional homesickness and what the Author defines a new kind of homesickness. The contradiction between those two types of attitude lies in the tension between longing for homeland and hatred of it. Hatred is manifested in rejection of the past and in forgetting that what was and was lost. The author expresses this contradiction using the difference between self-pity and self-destruction. In my analyzes I show how self-destruction contributes to transforming the real past into something that never was. Thus, the entire past transforms into spectral space.